Textbook of Microbiology and Immunology - Parija,Subhash Chandra (Elsevier, Relex India Pvt Ltd, 2016)
The third edition of the Textbook of Microbiology and Immunology provides fully updated text on the various aspects of microbiology and infectious diseases, which makes it the most authoritative and informative text in medical microbiology. It is a must-have book for preparing MBBS examination as well as the postgraduate entrance tests.